PENGARUH TEKNIK MARMET TERHADAP KELANCARAN ASI PADA IBU POST SECTIO CAESAREA DI RUMAH SAKIT GRANDMED LUBUK PAKAM - NOVITA BR GINTING MUNTHE; Desideria Yosepha Ginting; KHORI SILVIA SARAGIH (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2018)
The marmet technique is the basic technique that should be taught to the mother in 24 hours after the baby was born so that the mother is confident in facing all possible problems such as the problem of mild milk fluency. The purpose of this research was to know the influence of marmet technique on the fluency of breast milk in post Sectio Caesarea patients at Grandmed Hospital Lubuk Pakam 2017. This research is a type of quantitative research, with pre-experiment research design using one group pre test - post test. The population in this research were all patients who had undergone post Sectio Caesarea for two days at Grandmed Hospital Lubuk Pakam. The samples of the population as many as 10 people with sampling technique purposive sampling. The statistic test used paired simple T-test with 95% confidence level (α = 0,05). The result of this research showed that there was an influence of marmet technique on the fluency of breast milk on post Sectio Caesarea patient at Grandmed Hospital Lubuk Pakam with Value 0.029. It is expected to the nurse to be able to apply the implementation of marmet technique on the post sectio caesarea patients as a health education to fluency of breast milk.